Potential renoprotective effects and possible underlying mechanisms of angiotensin receptor-neprilysin inhibitors in cardiorenal syndrome - Rahman, Md. Moshiur; Rahman, Asadur; Nishiyama, Akira (Frontiers in Medicine, 2025)
Angiotensin receptor-neprilysin inhibitors (ARNIs) represent a novel class of medications characterized by their dual action on major cardiorenal regulators, specifically the renin–angiotensin system (RAS) and the natriuretic peptide (NP) system. Sacubitril/valsartan, a pioneering ARNI, has demonstrated strong antihypertensive effect as well as superior efficacy in preserving renal function compared to RAS inhibitors in heart failure patients with reduced ejection fraction. Here, we gathered evidence on the impact of sacubitril/valsartan on the preservation of kidney function in patients with cardiorenal syndrome (CRS). In particular, we present a comprehensive summary of the latest advancements and findings from clinical trials, studies, and meta-analyses on the impact of ARNIs in maintaining or improving renal function. We also discussed the pre-clinical evidence supporting the use of sacubitril/valsartan for improving renal function, along with the underlying molecular mechanisms in animal models mimicking various clinical scenarios. Altogether, the analysis of published data from both pre-clinical and clinical studies provides substantial support for the usefulness of ARNIs in enhancing renal protection in subjects with CRS.